Cultural genocide - Daniélou, Alain (International Library of African Music, 1969)
Instead of directing research towards what might be called "research into nonculture”, one should attempt, in collaboration with the cultural organizations of African countries, to make a systematic evaluation of the great cultural currents that have contributed to the development of the musical forms that exist on the African continent, and a serious study of the forms of musical language and communication that survive in Africa, as well as of the original artistic realizations which are their expression. For this we must undertake a complete study of the African continent, independent of state frontiers and ethnic and linguistic divisions, in order to investigate, after the cultural crisis caused by the colonial period, the survivals on the highest artistic and technical level of the musical forms peculiar to Africa, and to give them back the place they deserve in the musical creation of our time.
Keywords: Africa; Research; Ethnomusicology; Music; African Music